Geometric Redesign and Cut-and-Fill Volume Estimation of a Non-Compliant Mine Haul Road at Pit Banko Tengah A, South Sumatra - Dwi Lestari; Syari Rahma Yanti; Tri Gamela Saldy; Rangga Agung Pribadi Heriawan (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2026)
Mine haul roads must satisfy geometric standards to ensure safe and reliable heavy-equipment mobilization. This study evaluated the inactive Tesla haul road at Pit Banko Tengah A, South Sumatra, for reactivation using Komatsu HD-785 rigid dump trucks. Existing road geometry was assessed against operational standards, followed by 3D spatial redesign and cut-and-fill volume estimation in hilly terrain. The results showed that several straight segments require widening, with the largest correction reaching 7.93 m to meet the 24 m standard. Segment 5 also requires curve widening and superelevation correction, with actual superelevation of 0.064 m compared with the 1.223 m design requirement. Road grades remained within the 8% maximum limit. The redesign produced an excavation-dominant earthwork profile, consisting of 203.92 BCM of cut and 9.79 BCM of fill. These findings provide a practical basis for planning haul-road reactivation while aligning geometric compliance with earthwork requirements.